DNA methylation dynamics during pregnancy - Fradin, Delphine; Tost, Jorg; Busato, Florence; Mille, Clémence; Lachaux, Fanny; Deleuze, Jean-François; Apter, Gisèle; Benachi, Alexandra (Frontiers in Cell and Developmental Biology, 2023)
Pregnancy is a state of multiple physiological adaptations. Since methylation of DNA is an epigenetic mechanism that regulates gene expression and contributes to adaptive phenotypic variations, we investigated methylation changes in maternal blood of a longitudinal cohort of pregnant women from the first trimester of gestation to the third. Interestingly, during pregnancy, we found a gain of methylation in genes involved in morphogenesis, such as ezrin, while we identified a loss of methylation in genes promoting maternal-infant bonding (AVP and PPP1R1B). Together, our results provide insights into the biological mechanisms underlying physiological adaptations during pregnancy.